Favelofagia: the creation of a new literacy canon form the favela - Loria, Luana (2019)
The Bando Editorial Favelofágico is a literary collective and a non-profit publishing house from Manguinhos (Rio de Janeiro) born in 2015. The collective intends to promote authors from the peripheries who identify themselves with a counter hegemonic perspective with respect to the literary and social standard dominant canon, in order to build a counter-hegemonic literary movement, plural, politicized, engaged, free from the canons and searching for practice and transformation.